2013
DOI: 10.1103/physrevlett.110.136401
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Electron Capture and Reemission by the Divacancy via Charge Transient Positron Spectroscopy

Abstract: Electron capture during forward bias and reemission at zero bias by divacancies in the depletion region of a silicon diode structure at room temperature have been studied for the first time using monoenergetic positrons. The positron response increases essentially linearly with electron current, as a result of increased positron trapping by negatively charged divacancies. The measurements indicate that ≤1% of the divacancies become negatively charged in the steady state at a forward bias of 1 V. Changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42] More recent advances include the studies on the asymmetric stability of vacancy defects in GaSb, [43,44] the possibility of detecting and identifying small substitutional impurities such as Li Zn in ZnO and Be Ga in GaN, [45][46][47] and studying transient charge transfer phenomena induced by electrical or optical excitation of defects. [48,49] For more comprehensive reviews on studying point defect in metals and semiconductors with positron annihilation techniques, it is advisable to browse through recent reviews. [7,[50][51][52][53] Challenges in defect identification arise in multielement nondilute alloys and compounds for four main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42] More recent advances include the studies on the asymmetric stability of vacancy defects in GaSb, [43,44] the possibility of detecting and identifying small substitutional impurities such as Li Zn in ZnO and Be Ga in GaN, [45][46][47] and studying transient charge transfer phenomena induced by electrical or optical excitation of defects. [48,49] For more comprehensive reviews on studying point defect in metals and semiconductors with positron annihilation techniques, it is advisable to browse through recent reviews. [7,[50][51][52][53] Challenges in defect identification arise in multielement nondilute alloys and compounds for four main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The study of divacancies in silicon using the methods of the positron annihilation spectroscopy is an area of rather intensive activity (see, e.g., [5] and references therein). Having combined the data obtained by both the positron annihilation lifetime and Hall's effect measurements, we have estimated the positron trapping cross-section by divacancies and showed that the cascade phonon-assisted mechanism underlies its thermal dependency.…”
Section: Introductionmentioning
confidence: 99%